2009
DOI: 10.1073/pnas.0911948107
|View full text |Cite
|
Sign up to set email alerts
|

AP-1 homolog BZLF1 of Epstein–Barr virus has two essential functions dependent on the epigenetic state of the viral genome

Abstract: EBV, a member of the herpes virus family, is a paradigm for human tumor viruses and a model of viral latency amenable for study in vitro. It induces resting human B lymphocytes to proliferate indefinitely in vitro and initially establishes a strictly latent infection in these cells. BZLF1, related to the cellular activating protein 1 (AP-1) family of transcription factors, is the viral master gene essential and sufficient to mediate the switch to induce the EBV lytic phase in latently infected B cells. Enigmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
236
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(248 citation statements)
references
References 48 publications
11
236
0
1
Order By: Relevance
“…Genetic data suggested that the early expression of BZLF1 has a critical role in driving the proliferation of resting B cells (8). However, tvRNAs were previously not considered as a source of BZLF1 protein immediately after infection and before de novo transcription.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic data suggested that the early expression of BZLF1 has a critical role in driving the proliferation of resting B cells (8). However, tvRNAs were previously not considered as a source of BZLF1 protein immediately after infection and before de novo transcription.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have already described transcripts of EBV in primary B cells shortly after infection, but the origin of these RNAs was not further analyzed (8,26). We set out to determine the time when viral transcripts appear after infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After primary infection, BZLF1 is expressed very early in B cells. However, its early expression does not immediately initiate the EBV lytic cycle but promotes the proliferation of resting memory and naive B cells (Kalla et al, 2010). It is also very important for maintaining cell survival during the lytic phase.…”
Section: Introductionmentioning
confidence: 99%
“…Routes by which Zta activates gene expression have been documented for both viral and host promoters. Many promoters are targeted by the interaction of the sequence-specific DNA-binding domain of Zta with sequence-specific 7 nt DNA elements, termed ZREs (Adamson & Kenney, 1999;Bergbauer et al, 2010;Bhende et al, 2004Bhende et al, , 2005Broderick et al, 2009;Dickerson et al, 2009;Flower et al, 2011;Holley-Guthrie et al, 1990;Kalla et al, 2012Kalla et al, , 2010Karlsson et al, 2008;Kenney et al, 1989;Ramasubramanyan et al, 2012a, b;Sinclair, 2003;Sinclair et al, 1991;Woellmer et al, 2012). At least 32 distinct ZRE sequence variants are specifically recognized by Zta (Flower et al, 2011).…”
Section: Introductionmentioning
confidence: 99%